2001
DOI: 10.1002/1097-4636(2001)58:3<221::aid-jbm1011>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Vascular graft healing. II. FTIR analysis of polyester graft samples from implanted bi-grafts

Abstract: FTIR-ATR analysis has shown that the 4-step process for preclotting polyester vascular grafts results in a uniform and reproducible fibrin coating of the polyester fibers. Western blot analyses have shown that FN and VEGF are also present in this fibrin coating. FTIR-ATR analyses of explanted grafts indicate that, while the in vivo healing of these preclotted polyester grafts proceed through the inflammation, proliferation, and remodeling phases of normal wound healing, these phases are modified. Because the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Until 10 years ago, approximately 90% of prostheses in large animal models were as short as 5.571.2 cm (Dacron and expended polytetrafluoroethylene (ePTFE)) and 4.571.7 cm polyurethanes (PU), with a median implantation periods of 91.8717.3 days for Dacron grafts, 60.079.36 days for polytetrafluoroethylene (PTFE) grafts [11] and 907127.1 days for PU grafts. In more recent years, slightly longer grafts were implanted (64% were still shorter than 7 cm) and observation periods became shorter (medians: 28.078.9 and 14.0718.7 for ePTFE and Dacron, respectively) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In the small proportion of studies where truly long prostheses were implanted, they were either aorto-aortic [30][31][32][33][34][35], aorto-iliac [36][37][38][39] or aorto-femoral [40].…”
Section: Transanastomotic Endothelialization (Tae): Barking Up the Wrmentioning
confidence: 99%
See 2 more Smart Citations
“…Until 10 years ago, approximately 90% of prostheses in large animal models were as short as 5.571.2 cm (Dacron and expended polytetrafluoroethylene (ePTFE)) and 4.571.7 cm polyurethanes (PU), with a median implantation periods of 91.8717.3 days for Dacron grafts, 60.079.36 days for polytetrafluoroethylene (PTFE) grafts [11] and 907127.1 days for PU grafts. In more recent years, slightly longer grafts were implanted (64% were still shorter than 7 cm) and observation periods became shorter (medians: 28.078.9 and 14.0718.7 for ePTFE and Dacron, respectively) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In the small proportion of studies where truly long prostheses were implanted, they were either aorto-aortic [30][31][32][33][34][35], aorto-iliac [36][37][38][39] or aorto-femoral [40].…”
Section: Transanastomotic Endothelialization (Tae): Barking Up the Wrmentioning
confidence: 99%
“…Typically, almost all the vascular graft studies in the past chose graft diameters that were largely size matched or even smaller than the artery and thus did not undercut the critical cross-sectional ratio from which point intimal hyperplasia develops. For example, the estimated mean Q c s for interposition grafts ranged from 0.63 to 42.0 in dogs [14][15][16][17]23,42,[63][64][65][66] (60 cm, top) and experimental grafts in animals (in the majority of studies o6 cm; bottom). In most animal models, transanastomotic endothelial outgrowth (red) leads to complete surface endothelialization within weeks making it impossible to study transmural or blood-born endothelialization.…”
Section: Anastomotic Intimal Hyperplasia: Clinical Villain Experimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of ePTFE segments, retrieved at 1 and 3 h; 3, 5, 7, 10, and 14 days; and 4 and 8 weeks postimplantation, were analyzed by FTIR‐ATR. Empirical rules coupled with a number of experimental and theoretical studies7, 9–24 were used to assist in IR band assignments for these spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The growth factors measured were vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), and transforming growth factor beta (TGF‐β), and the cell adhesive protein fibronectin (FN), because these have been shown to be important in angiogenesis, endothelial cell proliferation, myointimal hyperplasia, smooth muscle cell growth, and wound healing 1–6. A Fourier‐transform infrared (FTIR) attenuated total reflectance (ATR) spectroscopy study of explanted segments of the preclotted PET portion of the bigraft indicated that the in vivo healing of the preclotted PET graft proceeded through the inflammation, proliferation, and remodeling phases of normal wound healing, forming an endothelialized surface, though these phases were modified 7…”
Section: Introductionmentioning
confidence: 99%